Technology transfer in the market with heterogeneous consumers - Shohei Yoshida; Cong Pan (Osaka University, Institute of Social and Economic Research (ISER), 2015)
The paper explains why some firms transfer their technology to competitors without direct compensation. We consider a Hotelling market where duopolists sell products with different qualities. This market consists of heterogeneous consumers, comprising two groups in terms of their valuations of product quality. We show that when consumers' preferences for product quality are sufficiently heterogeneous, a high-quality firm benefits from qualityenhancing technology transfer without payment. Furthermore, we extend the model to a circular city with four firms and show that a firm can benefit from a technology transfer to direct competitors rather than to an indirect competitor.
Keywords: L24; L41; M21; 330; Technology transfer; Competitor collaboration; Consumer heterogeneity